Paolo Canevari. - Camilleri, Andrea; Canevari, Paolo; Codognato, Mario; von Drathen, Doris; Iles, Chrissie; Magrelli, Valerio (Milano : Edizioni Charta Milano, 2002)
Paolo Canevari confronts classical tradition through a use of materials that belong to contemporary and popular culture : rubber, newspapers, comics. In the early nineties the artist lived, worked and exhibited in New York. He later participated in important exhibitions in Los Angeles, Paris, Kiev, Wien, Dublin, Bangkok. This volume surveys ten years of his work including Camera d'aria (Inner Tube) 1991, the cartoons, installations and most recent performances that testify to his philosophy, based on the impermanence of art, for which memory is the greatest monument of all.
bibliog. p. 159
biog., ind. tent., gr. tent. p. 157-158
Engels
Italiaans
boek
Keywords: Canevari, Paolo